2005
DOI: 10.1016/j.ijcard.2004.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of health related quality of life in paced patients

Abstract: With the tremendous advances in cardiac pacing during the past four decades, cardiac pacemaker implantation is now a common clinical procedure. In recent years, the indications for permanent pacemakers have expanded. This increase in reasons for pacing and shift in mode of pacing have been caused by the evolution of pacemaker therapy from a life-saving measure (mortality), to one aimed at improving healthrelated quality of life (HRQoL). Until now the efficacy of pacing therapy has predominantly been measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…Therefore, this study also showed a direct relationship of functional class, which reflects the degree of heart failure, quality of life in patients with pacemakers, confirming reports by other authors, such as Stofmeel et al [18] Oliveira et al [8,23]; Cunha et al [9].…”
Section: Quality Of Life X Functional Classificationsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, this study also showed a direct relationship of functional class, which reflects the degree of heart failure, quality of life in patients with pacemakers, confirming reports by other authors, such as Stofmeel et al [18] Oliveira et al [8,23]; Cunha et al [9].…”
Section: Quality Of Life X Functional Classificationsupporting
confidence: 90%
“…However, it is still debatable the correlation between functional class and quality of life of definitive cardiac pacemaker users. This question is the basis of this study, therefore, it is necessary to deeply discuss the theme "functional capacity and quality of life in patients with pacemaker", as suggested in studies by Stofmeel et al [18] Oliveira et al [8] and Cunha et al [9].…”
Section: Fc Qol Icdmentioning
confidence: 99%
“…In addition to thisq uestionnaire,H opp et al used separatequestionsmeasuring satisfaction with the telehealth equipmentf or the intervention group, with questionsfrom the National AmbulatoryC areS urvey, which theym odified for usei ne valuating telehealth services. Stofmeel et al [16] have developed andtested adisease-specificquestionnaire,Aquarel, for pacemaker patients, to investigateH RQoL.I tw as arguedt hat Aquarelcoversthe fullspectrumofrelevant outcomes, and can be used in addition to the SF-36 whichi sam ore genericH RQoL questionnaire.D oll et al [ 17] have formulatedamodel of End-User Computer Satisfaction as an instrument to evaluate systems to be compared, andDemiris hasdescribed importantp rinciplesi nd esign andt esting surveysfor telemedicine applications [18].…”
Section: Patients Acceptance and Clinical Outcomes In Telemedicinementioning
confidence: 99%
“…These changes are interesting; we found smaller positive intragroup differences than differences published in other QoL studies. Previous studies of QoL in patients with C‐PM showed important general improvements in QoL after implantation of a pacemaker, in terms of both physical and psychological health; however, the use of different tools to measure QoL makes comparisons difficult. We think our lower improvement can be explained by the mean age of our population (80 years), which is higher than the mean age in previous studies.…”
Section: Discussionmentioning
confidence: 99%